2012
DOI: 10.4236/ojemd.2012.24014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Dyslipidemia among Adults in Saudi Arabia: Results from a National Survey

Abstract: Data were collected and analyzed from a cross-sectional study using the World Health Organization's STEPwise approach, to estimate the prevalence of various types of dyslipidemia and determine their associated factors among adults in Kingdom of Saudi Arabia. The study population included 4490 Saudi adults aged 15 years and older who were selected by a stratified, multistage, cluster random sampling technique. Lipid profile was determined by spectrophotometrically by biochemical methods, high total cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
55
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 20 publications
22
55
4
Order By: Relevance
“…Low HDL was detected in 36.8% of participants. The results of the current study are in agreement with a previous study conducted in Saudi Arabia where the prevalence of dyslipidemia rate was in the range of 20-44% (Al-Kaabba et al, 2012), moreover, Saudi Arabia's STEP Report revealed that at least one fifth of the included population had high cholesterol level (Saudi Arabia STEP Report, 2005). Knowledge on the clustering pattern of NCDs risk factors may guide the design of more effective health promotion initiatives (de Costa et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Low HDL was detected in 36.8% of participants. The results of the current study are in agreement with a previous study conducted in Saudi Arabia where the prevalence of dyslipidemia rate was in the range of 20-44% (Al-Kaabba et al, 2012), moreover, Saudi Arabia's STEP Report revealed that at least one fifth of the included population had high cholesterol level (Saudi Arabia STEP Report, 2005). Knowledge on the clustering pattern of NCDs risk factors may guide the design of more effective health promotion initiatives (de Costa et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…These findings highlight the necessity for screening programs for early case detection and as initial platform for health education initiatives for NCDs prevention. Dyslipidemia is an important risk factor for many NCDs (Al-Kaabba et al, 2012) and there is some evidence of its association is associated with some cancers (Jafri and Karas, 2010 levels were detected in 32% and 36.6% respectively. Women had statistically significant higher levels of total cholesterol and TG than men.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of serum cholesterol were detected in a study carried out in Saudi Arabia on a population of about 4500 people, but the study included individuals aged 15 years and older. Mean TC levels were 172.1 mg/dL in females and 173.6 mg/dL in males, and LDL-C -107.0 mg/dL and 106.3 mg/dL, respectively [18]. The levels of TC found in the NATPOL 2011 survey are close to the levels found in the populations of developed North American and European countries.…”
Section: As Shown Insupporting
confidence: 52%
“…Even though it is estimated that up to 80% of deaths in developing countries are secondary to CVD, there is an absence of systematic epidemiological data on cardiovascular (CV) risk factors from these developing countries [3,4]. The majority of epidemiological studies from the developing world pre-date recent socioeconomic developments and are either too countryspecific or only recruited patients from specific healthcare settings (outpatients, specialist or acute care settings) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%